Extensive uterine deciduosis as cause for spontaneous hemoperitoneum in pregnancy - Monteiro,Diana Margarida (2022)
Abstract Ectopic decidualization is usually an incidental finding during surgical approach of a pregnant abdominal cavity. It presents as one or multiple friable and haemorrhagic lesions. We report a pregnant woman presenting with intense abdominal pain at 36 weeks and known placenta previa. During c-section, hemoperitoneum was observed originating on an exuberant friable and highly haemorrhagic lesion, covering the posterior uterine surface, both adnexal regions and the anterior wall of the rectum. Haemostasis was done with conservative measures and the patient had favourable outcome. Deciduosis is a benign entity and should be managed conservatively to prevent iatrogenic lesions.